A critical review on remediation of bisphenol S (BPS) contaminated water: Efficacy and mechanisms. Issue 5 (3rd March 2020) - Fang, Zheng; Gao, Yurong; Wu, Xiaolian; Xu, Xiaoya; Sarmah, Ajit K.; Bolan, Nanthi; Gao, Bin; Shaheen, Sabry M.; Rinklebe, Jörg; Ok, Yong Sik; Xu, Song; Wang, Hailong
Abstract: Bisphenols have drawn increasing attention from regulatory agencies and scientific communities due to their widespread occurrences, distribution and endocrine disrupting effects, and severe toxicity. As one of the bisphenol A (BPA) substitutes, bisphenol S (BPS) is most frequently detected in the environment. Although numerous studies have shown its occurrence, distribution, and toxicity to certain aquatic species, investigation on BPS removal from aqueous environments is lacking. Thus, in this review, we summarize the state-of-art about BPS removal approaches including biodegradation, sorption, and advanced oxidation processes. Particular attention has been paid to the BPS sorption mechanisms, active species for BPS biodegradation, and the corresponding degradation pathways. The primary degradation intermediates formed during BPS oxidation (e.g. p -hydroxybenzenesulfonic acid) are discussed. The effects of solution chemistry (pH, ionic strength, anion, and surfactants) on BPS decontamination are also emphasized. In addition, knowledge gaps, current challenges, and future research needs of BPS decontamination in real environments have been discussed briefly. Through this review we demonstrate the overarching scientific opportunities for a comprehensive understanding of the efficiency and mechanisms of the bio-and chemical remediation approaches of BPS contaminated water. Highlights: Microplastics may become a new source of bisphenol S (BPS) in aquatic environment. BPS is biodegradable but it may take a long time. Major mechanisms for BPS sorption are summarized and discussed. BPS degradation mechanisms and pathways are summarized. Graphical Abstract: UF0001